Prevalence and Impact of Workplace Bullying among Pharmacy Practice Faculty in the United States - Kristin Klein; Emma Dittmar; Sarah Vordenberg (University of Minnesota Libraries Publishing, 2023)
Objective: To identify the prevalence and impact of workplace bullying among pharmacy practice faculty in the United States. Methods: Members of the Pharmacy Practice section of the American Association of Colleges of Pharmacy were invited to complete an online survey about the frequency with which they experienced negative workplace behaviors in the communication, humiliation, manipulation, discrimination, and violence domains as well as workplace bullying in the previous 12 months. Independent t-tests and chi-squared tests were used to investigate associations between workplace bullying and pharmacy practice faculty demographic and employment characteristics. Results: Participants (n=256) reported a median of 6 negative behaviors in the workplace, most often in the communication and humiliation domains. A total of 50 (19.5%) reported experiencing workplace bullying. The most common impacts of workplace bullying included increasing their stress level (n=44/49, 89.8%), negative effects on their emotional health (n=42/49, 85.7%), and job dissatisfaction (n=40/49, 81.6%). Female participants more frequently reported workplace bullying (n=43/196, 21.9%) compared to male participants (n=4/56, 7.1%; p=0.012). Individuals who identified as white were less likely to report workplace bullying (n=40/233, 17.2%) compared to individuals of all other races (n=8/19, 42.1%; p=0.008). Conclusion: Most pharmacy practice faculty reported experiencing some degree of negative workplace behaviors during the past 12 months. Additional strategies are needed to create inclusive work environments with transparent, actionable policies when workplace bullying occurs.   Treatment of human subjects: IRB exemption granted